The Influence of Profitability, Liquidity, and Growth of Company on Dividend Policy (Study of Manufacturing Industrial Listed Company on the Indonesian Stock Exchange Period 2018 - 2022) - Paulus Sugianto Yusuf; R. Roosaleh Laksono T. Y; R. Ferry Mulyawan M. (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2024)
The research aims to investigate the impact of Profitability, Liquidity, and Company Growth on Dividend Policy in the manufacturing industry listed on the Jakarta Stock Exchange from 2018 to 2022. The Dividend Payout Ratio (DPR) is used as a proxy for dividend policy, while Return on Equity (ROE), Cash Ratio, and Dividend Growth per share are used as proxies for profitability, liquidity, and company growth, respectively. The research adopts a causal research approach using quantitative calculations. The research population includes all manufacturing industries listed on the Indonesia Stock Exchange during the 2018 - 2022 period. The sampling technique is based on a specific objective, and the data analysis involves multiple linear regressions, preceded by necessary tests. The data analysis is conducted using the SPSS (Statistical Package for the Social Sciences) computer program. The results indicate that profitability (ROE) and liquidity (Cash Ratio) do not affect dividend policy (DPR), whereas company growth (dividend growth per share) influences dividend policy (DPR) for manufacturing companies listed on the Indonesian Stock Exchange from 2018 to 2022.